Kant's little Prussian head and other reasons why I write : an autobiography in essays - Messud, Claire, 1966- (W. W. Norton & Company, 2020)
"A glimpse into a beloved novelist's inner world, shaped by family, art, and literature. In her fiction, Claire Messud "has specialized in creating unusual female characters with ferocious, imaginative inner lives" (Ruth Franklin, New York Times Magazine). Kant's Little Prussian Head and Other Reasons Why I Write opens a window on Messud's own life: a peripatetic upbringing; a warm, complicated family; and, throughout it all, her devotion to art and literature. In twenty-nine intimate, brilliant, funny, and sharp essays, Messud reflects on a childhood move from her Connecticut home to Australia; the complex relationship between her modern Canadian mother and a fiercely single French Catholic aunt; and a trip to Beirut, where her pied-noir father had once lived, while he was dying. She meditates on Albert Camus, Teju Cole, and Valeria Luiselli, and tours her favorite paintings at Boston's Museum of Fine Arts. Crafting a vivid portrait of a life in celebration of the power of literature, Messud proves once again "an absolute master storyteller" (Rebecca Carroll, Los Angeles Times)"--